Composite material as well as preparation method and application thereof
By spraying organic and inorganic microparticles on the surface of platinum silicone to form composite materials, the problems of cumbersome preparation process and insufficient performance of existing superhydrophobic materials are solved, and high hydrophobicity, stability and durability are achieved, and suitable for a variety of application fields. .
Patent Information
- Application Number
- CN202411235762.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-05
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-10
AI Technical Summary
The preparation process of existing superhydrophobic materials is complicated, and there are problems such as insufficient hydrophobic performance, poor stability, insufficient durability and poor adaptability to bending.
Platinum silicone is used as the matrix, and composite materials are formed on the surface by spraying organic and/or inorganic microparticles. A simple particle spraying process is carried out using the two-component curing characteristics of platinum silicone to form a mastoid structure similar to the surface of lotus leaves, thereby Improve surface roughness and hydrophobic properties.
It has achieved high hydrophobicity, good stability and durability, and has good adaptability to bending. It is suitable for droplet collection, waterproofing and corrosion-proof treatment, and is suitable for construction, automobile, aircraft shell and other fields.
Smart Images

Figure CN119286036A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of hydrophobic materials, and in particular to a composite material and a preparation method and application thereof. Background Art
[0002] Super-hydrophobic material is a new type of material, which is widely used in various fields. With the increase of super-hydrophobic material applications, its preparation method continues to be studied. Chemical reagents are usually used to treat the surface of the material to cause a chemical reaction on the surface to form a hydrophobic surface. However, in the preparation process, multiple and complex physical processes or chemical reagents are mostly required, which leads to the cumbersome preparation of super-hydrophobic materials and even produces a large amount of chemical waste liquid. In addition, super-hydrophobic materials in the prior art also have problems such as poor adaptability to bending, poor stability, and insufficient durability. Summary of the invention
[0003] The purpose of the present invention is to overcome the problems of insufficient hydrophobicity and poor stability of hydrophobic materials in the prior art, and to provide a composite material and a preparation method and application thereof, wherein the composite material has high hydrophobicity and exhibits good stability and durability.
[0004] In order to achieve the above object, the present invention provides a composite material, which includes a matrix and a particle layer composited on the surface of the matrix; the matrix is platinum silica gel;
[0005] The particle layer is composed of organic and / or inorganic micron particles;
[0006] The static contact angle of the composite material is not less than 130°.
[0007] A second aspect of the present invention provides a method for preparing a composite material, comprising:
[0008] (1) spraying organic and / or inorganic micron particles onto the surface of a platinum silica precursor;
[0009] (2) solidifying the product obtained in step (1).
[0010] The third aspect of the present invention provides a composite material obtained by the above preparation method.
[0011] The fourth aspect of the present invention provides use of the composite material described in the first aspect or the third aspect in droplet collection, waterproof and anti-corrosion treatment or super-hydrophobic surface coating.
[0012] The composite material provided by the present invention includes platinum silica gel and a particle layer composited on the surface of platinum silica gel. The material has high hydrophobicity and a static contact angle of not less than 130°. The reason may be that the organic and / or inorganic micron particles on the surface of platinum silica gel form a papillary structure similar to the surface of a lotus leaf. This structure increases the roughness of the surface of platinum silica gel, thereby making it super-hydrophobic, so that liquid cannot stay on the surface and is easily drained away. Preferably, the composite material exhibits good stability, durability and adaptability to bending.
[0013] The preparation method of the composite material provided by the present invention utilizes the two-component curing characteristics of platinum silica gel and composites the micron particles on the surface of platinum silica gel through a simple particle spraying process. The steps are simple, no additional chemical reagents need to be added, and the needs of large-scale production can be met.
[0014] The composite material provided by the present invention has excellent hydrophobic properties, can be used in the process of collecting rainwater, preparing drinking water, desalinating seawater, etc., and can also form a self-repairing waterproof layer or anti-corrosion layer, and can be used in buildings, automobiles, aircraft shells, etc. In addition, the composite material uses platinum silica gel as a base material, has good antibacterial properties, corrosion resistance, etc., is biodegradable, and can be used as a hydrophobic coating in the fields of medical treatment, food processing, optical instruments, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a preparation process of a composite material in one embodiment of the present invention;
[0016] Figure 2 is a comparison of contact angles of the composite material prepared in Example 1 of the present invention before and after the stretching and washing treatment;
[0017] Figure 3 This is the water droplet sliding process of the composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0018] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0019] The first aspect of the present invention provides a composite material, comprising a matrix and a particle layer composited on the surface of the matrix; the matrix is platinum silica gel;
[0020] The particle layer is composed of organic and / or inorganic micron particles;
[0021] The static contact angle of the composite material is not less than 130°.
[0022] The composite material provided by the present invention includes platinum silica gel and a particle layer composited on the surface of platinum silica gel. The material has high hydrophobicity and a static contact angle of not less than 130°. The reason may be that the organic and / or inorganic micron particles on the surface of platinum silica gel form a papillary structure similar to the surface of a lotus leaf. This structure increases the roughness of the surface of platinum silica gel, thereby making it super-hydrophobic, so that liquid cannot stay on the surface and is easily drained away. Preferably, the composite material exhibits good stability, durability and adaptability to bending.
[0023] According to the present invention, preferably, the static contact angle of the composite material is not less than 150°, preferably 150-165°, for example, it can be 150°, 151°, 152°, 153°, 154°, 155°, 156°, 157°, 158°, 159°, 160°, 161°, 162°, 163°, 164°, 165° and other typical contact angles or ranges therebetween.
[0024] According to the present invention, preferably, the static contact angle of the platinum silica gel is not less than 80°, preferably 80-100°, for example, it can be 80°, 85°, 90°, 95°, 100° or other typical but non-limiting static contact angles.
[0025] In the present invention, the static contact angle is measured by a contact angle meter (SDC-350).
[0026] The present invention has no particular limitation on the source of the platinum silica gel, and it can be prepared by commercially available platinum silica gel products or any method known in the art. Platinum silica gel is a two-component silica gel, which is divided into agent A and agent B. Preferably, the platinum silica gel is obtained by curing a precursor of platinum silica gel, and the precursor of the platinum silica gel is obtained by mixing agent A and agent B; preferably, the mass ratio of agent A to agent B of the platinum silica gel is 1-5:5-1.
[0027] In the present invention, the platinum silica gel in the composite material refers to the product obtained by mixing and curing agent A and agent B.
[0028] According to some preferred embodiments of the present invention, the platinum silica gel is Ecoflex platinum silica gel (purchased from SMOOTH-ON, USA). The platinum silica gel has a high static contact angle, can directly contact human skin, has biodegradable properties, is conducive to improving the hydrophobicity of the composite material, and is environmentally friendly.
[0029] According to the present invention, preferably, the average particle diameter of the micron particles is 1-100 μm, for example, it can be 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 85 μm, 90 μm, 95 μm, 100 μm and other typical but non-limiting diameter values or ranges therebetween. Preferably, the average particle diameter of the micron particles is 10-50 μm, more preferably 20-40 μm. Within the above preferred particle diameter range, it is beneficial to further improve the hydrophobicity of the composite material.
[0030] The present invention has a wide range of choices for the composition of the organic and / or inorganic micronized particles. As long as the organic and / or inorganic micronized particles are insoluble in the matrix and do not react with the matrix, they can be applied to the present invention.
[0031] According to the present invention, preferably, the inorganic micron particles are selected from at least one of metal oxides, metal nitrides, non-metallic elements, and non-metallic oxides; preferably at least one of titanium dioxide, silicon dioxide, gallium nitride, carbon black, monocrystalline silicon, and polycrystalline silicon, and more preferably silicon dioxide.
[0032] Preferably, the organic micron particles are polymer powders, preferably at least one selected from fluorinated ethylene propylene copolymer, polytetrafluoroethylene, polyvinyl chloride, and more preferably fluorinated ethylene propylene copolymer.
[0033] The present invention has no particular requirements on the source of the organic and / or inorganic micronized particles, which may be purchased from commercial sources as long as they meet the above average particle diameter range.
[0034] The present invention has no special requirements for the uniformity of the particle layer, as long as the organic and / or inorganic micron particles are relatively uniformly covered. According to the present invention, preferably, the average thickness of the particle layer is 1 μm-5 mm, for example, it can be 1 μm, 10 μm, 20 μm, 50 μm, 100 μm, 200 μm, 500 μm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, etc., which are typical but non-limiting average thickness values or ranges therebetween. Preferably, the average thickness of the particle layer is 10 μm-2 mm, and more preferably 20 μm-1.5 mm.
[0035] In the present invention, the average thickness of the particle layer is obtained by scanning electron microscopy.
[0036] A second aspect of the present invention provides a method for preparing a composite material, comprising:
[0037] (1) spraying organic and / or inorganic micron particles onto the surface of a platinum silica precursor;
[0038] (2) solidifying the product obtained in step (1).
[0039] The preparation method of the composite material provided by the present invention utilizes the two-component curing characteristics of platinum silica gel and composites the micron particles on the surface of platinum silica gel through a simple particle spraying process. The steps are simple, no additional chemical reagents need to be added, and the needs of large-scale production can be met.
[0040] Preferably, the precursor of the platinum silica gel is obtained by mixing agent A and agent B of platinum silica gel. The present invention has a wide range of selection for the dosage of agent A and agent B of the platinum silica gel, as long as platinum silica gel can be obtained by curing, and those skilled in the art can make a selection according to actual needs. According to some preferred embodiments of the present invention, the mass ratio of agent A to agent B of the platinum silica gel is 1-5:5-1, for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 2:1, 3:1, 4:1, 5:1 and other typical but non-limiting ratios or ranges between the two.
[0041] According to the present invention, preferably, the preparation method further comprises: subjecting the mixture of agent A and agent B of platinum silica gel to vacuum degassing treatment to remove internal bubbles. Preferably, the conditions of the vacuum degassing treatment include: vacuum degree of 0-5000Pa, and treatment time of 1-10min.
[0042] According to some preferred embodiments of the present invention, the average particle diameter of the micron particles is 1-100 μm, preferably 10-60 μm, for example, it can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm and other specific but non-limiting particle size values or any range between two, further preferably 20-60 μm, more preferably 20-40 μm.
[0043] According to some preferred embodiments of the present invention, the inorganic micron particles are selected from at least one of metal oxides, metal nitrides, non-metallic elements, and non-metallic oxides; preferably at least one of titanium dioxide, silicon dioxide, gallium nitride, carbon black, monocrystalline silicon and polycrystalline silicon, and more preferably silicon dioxide.
[0044] Preferably, the organic micron particles are polymer powders, preferably at least one selected from fluorinated ethylene propylene copolymer, polytetrafluoroethylene, polyvinyl chloride, more preferably fluorinated ethylene propylene copolymer.
[0045] According to some preferred embodiments of the present invention, step (1) comprises: spraying organic and / or inorganic micron particles onto the surface of the platinum silica gel precursor through a nozzle; for example, the spraying can be performed using a powder spray bottle or the like.
[0046] According to some preferred embodiments of the present invention, the spraying amount of the organic and / or inorganic micron particles is such that the thickness of the particle layer formed by spraying is 1 μm-5 mm, preferably 10 μm-2 mm, and more preferably 20 μm-1.5 mm.
[0047] According to some preferred embodiments of the present invention, the curing conditions include: temperature of 10-80° C. and time of 1-10 h.
[0048] According to some preferred embodiments of the present invention, the preparation method further comprises: washing the product obtained in step (2) to remove excess micron particles on the surface. The washing can be performed using conventional methods and conditions in the art, for example, by washing the surface of the product with water.
[0049] The third aspect of the present invention provides a composite material obtained by the above preparation method.
[0050] The fourth aspect of the present invention provides use of the composite material described in the first aspect or the third aspect in droplet collection, waterproof and anti-corrosion treatment or super-hydrophobic surface coating.
[0051] The composite material provided by the present invention has excellent hydrophobic properties, can be used in the process of collecting rainwater, preparing drinking water, desalinating seawater, etc., and can also form a self-repairing waterproof layer or anti-corrosion layer, and can be used in buildings, automobiles, aircraft shells, etc. In addition, the composite material uses platinum silica gel as a base material, has good antibacterial properties, corrosion resistance, etc., is biodegradable, and can be used as a hydrophobic coating in the fields of medical treatment, food processing, optical instruments, etc.
[0052] The present invention will be described in detail below through examples.
[0053] The platinum silica gel used in the following examples is Ecoflex platinum silica gel (purchased from SMOOTH-ON, USA).
[0054] Example 1
[0055] The main preparation process is as follows Figure 1 shown.
[0056] Ecoflex glue A and Ecoflex glue B with a mass ratio of 1:1 were mixed into a container and stirred evenly. The uncured Ecoflex was then placed in a vacuum chamber (vacuum degree of 1000Pa) for five minutes to remove internal bubbles to obtain a matrix precursor. Silica particles were then sprayed onto the surface of the matrix precursor through a powder spray bottle, and the average particle size of the silica particles was 30 microns, and then cured at room temperature for 6 hours.
[0057] After curing, the excess silicon dioxide particles were shaken off and the surface was rinsed with deionized water to obtain composite material A1. The average thickness of the silicon dioxide layer was 40 μm.
[0058] Example 2
[0059] Ecoflex glue A and Ecoflex glue B with a mass ratio of 1:1 were mixed into a container and stirred evenly. The uncured Ecoflex was then placed in a vacuum chamber (vacuum degree of 1000 Pa) for five minutes to remove internal bubbles to obtain a matrix precursor. Fluorinated ethylene propylene copolymer particles (purchased from Shuangfu Plastic Raw Materials Co., Ltd.) were then sprayed onto the surface of the matrix precursor through a powder spray bottle. The average particle size of the particles was 60 microns, and then cured at 15°C for 10 hours.
[0060] After curing, the excess fluorinated ethylene propylene copolymer particles were shaken off and the surface was rinsed with deionized water to obtain composite material A2. The average thickness of the particle layer was 100 μm.
[0061] Example 3
[0062] Ecoflex glue A and Ecoflex glue B with a mass ratio of 1:1 were mixed into a container and stirred evenly. The uncured Ecoflex was then placed in a vacuum chamber (vacuum degree of 1000Pa) for five minutes to remove internal bubbles to obtain a matrix precursor. Silica particles were then sprayed onto the surface of the matrix precursor through a powder spray bottle, and the average particle size of the silica particles was 40 microns, and then cured at 60°C for 2 hours.
[0063] After the curing was completed, the excess silicon dioxide particles were shaken off and the surface was washed with deionized water to obtain the composite material A3. The average thickness of the particle layer was 500 μm.
[0064] Example 4
[0065] The method of Example 1 is followed, except that the average particle diameter of the silicon dioxide particles used is 5 μm.
[0066] After the curing was completed, the excess silicon dioxide particles were shaken off and the surface was washed with deionized water to obtain the composite material A4. The average thickness of the particle layer was 8 μm.
[0067] Example 5
[0068] The method of Example 1 was followed, except that polycrystalline silicon particles with an average particle size of 100 microns were used instead of silicon dioxide to obtain composite material A5. The average thickness of the particle layer was 1.5 mm.
[0069] Example 6
[0070] The composite material A6 was obtained by following the method of Example 1, except that carbon black particles with an average particle size of 1 μm were used instead of silicon dioxide. The average thickness of the particle layer was 10 μm.
[0071] Comparative Example 1
[0072] Ecoflex glue A and Ecoflex glue B with a mass ratio of 1:1 were mixed into a container and stirred evenly. The uncured Ecoflex was then placed in a vacuum chamber (vacuum degree of 1000 Pa) for five minutes to remove internal bubbles to obtain a matrix precursor. It was then cured at room temperature for 6 hours to obtain a composite material DA1.
[0073] Performance Testing
[0074] Static contact angle test: The contact angles of the composite materials prepared in the above embodiments and comparative examples were tested by a contact angle meter (SDC-350). The results are shown in Table 1.
[0075] The contact angles of the unmodified Ecoflex platinum silica gel DA1, the composite material A1 and the composite material A1 after 50% stretching and washing for 5000 cycles are shown in FIG. Figure 2 As shown. The static contact angle of the composite material A1 is 157°. By comparison, it can be seen that, relative to the Ecoflex platinum silica gel without surface modification, the hydrophobicity of the composite material prepared by the present invention is greatly improved, and it has good super-hydrophobicity. The composite material A1 is stretched to 150% of its length and then relaxed to its natural length, and washed with water. After this process is repeated for 5000 cycles, the contact angle of the super-hydrophobic surface hardly changes. Therefore, the composite material provided by the present invention has good stability and durability.
[0076] Table 1
[0077] serial number Static contact angle (°) Contact angle after 50% stretch cleaning (°) A1 157.6 156.2 A2 151.0 / A3 154.0 / A4 138.6 / A5 139.5 / A6 142.1 / DA1 109.6 /
[0078] Water drop test:
[0079] Test results such as Figure 3 As shown, Figure 3 (a) is the water drop sliding condition of Ecoflex platinum silicone without surface modification. Figure 3 (b) shows the water drop sliding down of composite material A1. Figure 3 (c) is when the curvature is 250m -1 Water droplet sliding down on composite material A1 under bending.
[0080] from Figure 3 (a) and Figure 3From the comparison of (b), it can be seen that when a 10 μL water droplet slides down the inclined superhydrophobic surface, the droplet on the surface of composite material A1 can easily slide down from the surface with an inclination angle of 15° compared with the unmodified Ecoflex platinum silica gel.
[0081] from Figure 3 (c) It can be seen that when the super-hydrophobic surface has a curvature of 250 μm -1 Under the bending, water droplets can also slide off, and the super hydrophobicity of the surface can continue to be maintained. Therefore, the composite material provided by the present invention has excellent bending adaptability.
[0082] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A composite material, characterized in that: The composite material comprises a matrix and a particle layer composited on the surface of the matrix; the matrix is platinum silica gel; The particle layer is composed of organic and / or inorganic micron particles; The static contact angle of the composite material is not less than 130°.
2. The composite material according to claim 1, wherein The static contact angle of the composite material is not less than 150°, preferably 150-165°.
3. The composite material according to claim 1 or 2, wherein: The static contact angle of the platinum silica gel is not less than 80°, preferably 80-100°; Preferably, the platinum silicone is Ecoflex platinum silicone; Preferably, the platinum silica gel is obtained by curing a precursor of platinum silica gel, and the precursor of platinum silica gel is obtained by mixing agent A and agent B; Preferably, the mass ratio of agent A to agent B of the platinum silica gel is 1-5:5-1.
4. The composite material according to any one of claims 1 to 3, wherein: The average particle diameter of the micron particles is 1-100 μm, preferably 10-60 μm, and more preferably 20-60 μm.
5. The composite material according to any one of claims 1 to 4, wherein: The inorganic micron particles are selected from at least one of metal oxides, metal nitrides, non-metallic elements, and non-metallic oxides; preferably at least one of titanium dioxide, silicon dioxide, gallium nitride, carbon black, single crystal silicon, and polycrystalline silicon; Preferably, the organic micron particles are polymer powders, preferably at least one selected from fluorinated ethylene propylene copolymer, polytetrafluoroethylene, and polyvinyl chloride.
6. The composite material according to any one of claims 1 to 5, wherein: The average thickness of the particle layer is 1 μm-5 mm, preferably 10 μm-2 mm, and more preferably 20 μm-1.5 mm.
7. A method for preparing a composite material, comprising: (1) spraying organic and / or inorganic micron particles onto the surface of a platinum silica precursor; (2) solidifying the product obtained in step (1).
8. The preparation method according to claim 7, wherein: The precursor of the platinum silica gel is obtained by mixing agent A and agent B, and the mass ratio of agent A to agent B of the platinum silica gel is 1-5:5-1; Preferably, the average particle diameter of the micron particles is 1-100 μm, preferably 10-50 μm, and more preferably 20-40 μm; Preferably, the inorganic micron particles are selected from at least one of metal oxides, metal nitrides, non-metallic elements, and non-metallic oxides; preferably at least one of titanium dioxide, silicon dioxide, gallium nitride, single crystal silicon, and polycrystalline silicon; Preferably, the organic micron particles are polymer powders, preferably at least one selected from fluorinated ethylene propylene copolymer, polytetrafluoroethylene, and polyvinyl chloride.
9. The preparation method according to claim 7 or 8, wherein: Step (1) comprises: spraying organic and / or inorganic micron particles onto the surface of the platinum silica precursor through a nozzle; Preferably, the spraying amount of the organic and / or inorganic micron particles is such that the average thickness of the particle layer formed by spraying is 1 μm-5 mm, preferably 10 μm-2 mm, and more preferably 20 μm-1.5 mm.
10. The preparation method according to any one of claims 7 to 9, wherein: The curing conditions include: temperature of 10-80°C and time of 1-10h; Preferably, the preparation method further comprises: washing the product obtained in step (2) to remove excess micron particles on the surface.
11. The composite material obtained by the preparation method according to any one of claims 7 to 10.
12. Use of the composite material according to any one of claims 1 to 6 or 11 in droplet collection, waterproofing and anti-corrosion treatment or super-hydrophobic surface coating.
Citation Information
Cited By
Temperature response type bionic anti-scaling coating and preparation method thereof
CN120718540A